Comparing 5G indoor wireless technologies: optical vs ultraviolet communication - Izzah Hazirah Zainal; Zaiton Abdul Mutalip; Haziezol Helmi Mohd Yusuf; Nurmala Irdawaty Hassan; Zeina Rihawi (International Journal of Advances in Applied Sciences, 2024)
Wireless communication technologies have become one of the biggest technologies that are considered suitable for radio frequency in various types of applications, including indoor applications. This study investigates the differences between optical wireless communication (OWC) and ultraviolet wireless communication (UVC). Several parameters are simulated, including bit error rate (BER), signal-to-noise ratio (SNR), data rate, and received power, to compare the performance of each technology in various scenarios. Owing to its wide bandwidth, license-free frequency spectrum, and low signal attenuation at low carrier frequencies, the OWC is suitable for radio frequency applications in many situations, including indoor environments. The simulation results show that UVC outperformed OWC in terms of BER and SNR. Moreover, UVC has a higher data transmission rate of up to 1.1 Gbps, making it a suitable technology for 5G communication.